Implementation of Processed Sago (Kapurung) on Diabetes Mellitus Type 2 Patients - Muda, Iskandar; Ramadhan, Andry; Sukmana, Mayusef; Khumaidi, Khumaidi (Jurnal Kesehatan Pasak Bumi Kalimantan, 2024)
Introduction: Diabetes mellitus (DM) is a chronic metabolic condition characterized by either the pancreas' failure to make enough insulin or the body's inability to adequately use the insulin that is produced. Diabetes type 2 is linked to lifestyle patterns, emphasizing the importance of leading a healthy lifestyle, such as eating meals with a low Glycemic Index. Sago is one of the foods with a low glycemic index that can help lower blood glucose levels. The purpose of this study is to know implementation of processed sago (Kapurung) on  diabetes mellitus type 2 patients Methods: The research methodology employed a descriptive method, with a case study approach conducted on four respondents who met the inclusion criteria of type 2 diabetes patients, female gender, aged 21-45 years. Results: The results showed that the first respondent (R1) had fasting blood sugar levels of 187 mg/dL, the second respondent (R2) had 116 mg/dL, the third respondent (R3) had 237 mg/dL, and the fourth respondent (R4) had 267 mg/dL after two hours of consuming processed sago. Conclusion: Patients with type 2 diabetes mellitus experienced changes in blood sugar levels after being administered processed sago; three responders had an increase in blood sugar levels, while one had a decrease